Kilometer-scale Kaiser effect identified in Krafla volcano, Iceland - Heimisson, Elías Rafn; Einarsson, Páll; Sigmundsson, Freysteinn; Brandsdóttir, Bryndís (Geophysical Research Letters, 2015)
The Krafla rifting episode in 1975 – 1984, consisted of around 20 inflation-deflation events within the Krafla caldera, where magma accumulated during inflation periods and was intruded into the transecting fissure swarm during brief periods of deflation. We reanalyze geodetic and seismic data from the rifting episode and perform a time-dependent inversion of a leveling time series for a spherical point source in an elastic half-space. Using the volume change as a proxy for stress shows that during inflation periods the seismicity rate remains low until the maximum inflation of previous cycles is exceeded thus exhibiting the Kaiser effect. Our observations demonstrate that this phenomenon, commonly observed in small-scale experiments, is also produced in kilometer-scale volcanic deformation. This behavior sheds new light on the relationship between deformation and seismicity of a deforming volcano. As a consequence of the Kaiser effect, a volcano may inflate rapidly without significant changes in seismicity rate.